Factors influencing perceived usefulness & ease of use of digital library technology by post-graduate students in Malaysia - Goon, Tuck Lee (2004)
This project aims to study the factors that influence the perceived ease of use and perceived usefulness of digital library technology by post-graduate students in Malaysia. Based on the data collected from 140 full-time and part-time students, this study examined the model involving perceived ease of use, perceived usefulness, interface characteristics, individual differences, and organisational context. It tested the notion whether interface characteristics have an impact on perceived ease of use.